2019
DOI: 10.3389/fmars.2019.00367
|View full text |Cite
|
Sign up to set email alerts
|

Global Observational Needs and Resources for Marine Biodiversity

Abstract: The diversity of life in the sea is critical to the health of ocean ecosystems that support living resources and therefore essential to the economic, nutritional, recreational, and health needs of billions of people. Yet there is evidence that the biodiversity of many marine habitats is being altered in response to a changing climate and human activity. Understanding this change, and forecasting where changes are likely to occur, requires monitoring of organism diversity, distribution, abundance, and health. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
92
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(92 citation statements)
references
References 115 publications
0
92
0
Order By: Relevance
“…Habitat suitability projections can help in developing research agendas that confirm and advance the model outputs and clarify the roles of predictor variables in determining species distributions. Incorporating these needs into the Deep Ocean Observing Strategy can help fill data gaps, and prioritize spatial locations for the collection of key physical and biogeochemical data (Canonico et al, ; Levin et al, ). As forward‐looking international entities, the United Nations’ Decade for Ocean Science, the Global Ocean Observing System, and the Regular Process for Global Reporting and Assessment of the State of the Marine Environment (a.k.a.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Habitat suitability projections can help in developing research agendas that confirm and advance the model outputs and clarify the roles of predictor variables in determining species distributions. Incorporating these needs into the Deep Ocean Observing Strategy can help fill data gaps, and prioritize spatial locations for the collection of key physical and biogeochemical data (Canonico et al, ; Levin et al, ). As forward‐looking international entities, the United Nations’ Decade for Ocean Science, the Global Ocean Observing System, and the Regular Process for Global Reporting and Assessment of the State of the Marine Environment (a.k.a.…”
Section: Discussionmentioning
confidence: 99%
“…For example, cold-water coral and fish distributions respond to small-scale variation in terrain, such as substrate type and seabed rugosity, as well as local oceanographic conditions such as food availability (Bennecke & Metaxas, 2017;De Clippele et al, 2017;Drazen et al, 2012;Rengstorf et al, 2013;Ross et al, 2015;White et al, 2005). We also recognize some limitations from the quantity, quality and spatial coverage of occurrence data, availability of absence records as well as some uncertainty in deepsea species identification (mostly for cold-water corals Incorporating these needs into the Deep Ocean Observing Strategy can help fill data gaps, and prioritize spatial locations for the collection of key physical and biogeochemical data (Canonico et al, 2019;Levin et al, 2019). As forward-looking international entities, This application is especially relevant for dramatic changes such as those projected here.…”
Section: Discussionmentioning
confidence: 99%
“…The Earth's oceans are under increasing environmental stress, and there have been calls for increased biomonitoring to understand these changes and (Canonico et al 2019). Unfortunately, conventional observation-based techniques of biomonitoring are infeasible at such scales.…”
Section: Introductionmentioning
confidence: 99%
“…At the scale of global coastal marine ecosystems, several environmental pressures act simultaneously, each having its own spatial resolution and temporal dynamics. Halpern et al (2008) and Crain et al (2009) found that no fewer than five pressures overlap anywhere in the world's oceans. Potential cumulative and/or interactive effects need to be addressed, for example by considering the following.…”
Section: The Real World: a Mixture Of Threats And Disturbances At Smamentioning
confidence: 99%